The Effect of Work Environment, Discipline and Motivation on the Performance of Elementary School Teachers in Gunungwungkal District - Hariyasasti, Yayuk (Faculty of Science and Technology University of Pramita Indonesia, 2025)
This study aims to analyze the relationship between the work environment and teacher performance in elementary schools in Gunungwungkal District, the influence of work discipline on teacher performance in elementary schools in Gunungwungkal District. The influence of motivation on teacher performance in elementary schools in Gunungwungkal District. The research method used is quantitative descriptive through a survey. Data collection was carried out through questionnaires distributed to 64 elementary school teachers in Gunungwungkal District which were determined by the simple random sampling method, research data were obtained by distributing questionnaires online through social media. Data analysis using structural equality modeling (SEM). The results of the study showed that there was a positive and significant influence between competence on teacher performance and work culture had a significant effect on teacher performance.